Can reducing carbon emissions improve economic performance: Evidence from China - Fei Yang; Beibei Shi; Ming Xu; Chen Feng (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
As the problem of carbon emissions is becoming increasingly more serious around the world, how to balance carbon emissions reduction and economic growth has become an important issue in the field of environmental economics. China is the world's largest carbon dioxide emitter, and China's Low-Carbon Pilot (CLCP) policy has significantly reduced carbon dioxide emissions and achieved expected benefits. However, is environmental quality improving at the expense of economic growth? This article selects macro panel data of 286 Chinese prefecture-level cities and micro data of Chinese industrial enterprises from 2001 to 2013, takes the CLCP policy implementation by five provinces and eight cities as a quasi-natural experiment, uses difference-in-differences (DID) method to investigate the causal effect of CLCP policy on regional economic growth and enterprise behavior. The results are as follows. First, the CLCP policy significantly promotes regional economic growth. Moreover, as the implementation time of the policy continues, environmental regulation has a greater effect of promoting economic growth. Second, although the CLCP policy significantly increases various production costs, it also promotes the growth of enterprises' output and benefits. Third, under the pressure of enterprise cost increase caused by environmental regulation, enterprises choose the positive way of strengthening internal management, improving efficiency and increasing innovation instead of choosing the negative way of trans-regional transfer, and finally achieve an improvement in output and benefits.
http://dx.doi.org/10.7910/DVN/SH8HRT
Keywords: O12; O13; Q38; 330; CLCP policy; economic growth; behavior of enterprise; DID